Autistic spectrum disorders educational and clinical interventions - Wahlberg, Tim. (Amsterdam ; New York : JAI, 2001)
This work is concerned with the study of children and adults with Autistic Spectrum Disorders (ASD). The book provides theoretical, educational and clinical perspectives related to this disorder. The perspectives discussed are based upon past and present theories of autism, educational practices since the 1970s and recent clinical innovations. The term ASD recognizes that this is a very heterogeneous disorder that encompasses the classic autistic disorder and milder variants such as Asperger syndrome and pervasive developmental disorder not otherwise specified. Presently, there exists a growing need for information to understand the complex educational and mental health needs of individuals with ASD. The content of this book is directed at meeting this need. For example, Section I of this book provides the reader with information concerned with theoretical foundations on the disorder and includes chapters on cognitive theories and symptomology of autism and neurological implications of autism to the ageing process. Section II provides the reader with educational best practices and includes chapters on pre-service and in-service training of teachers, successful curriculum innovations, and multicultural concerns. Section III of the book provides the reader with recent effective clinical practices and includes chapters on assessment, counselling techniques for individuals with ASD, a model of how to work with parents of children with ASD, psychotropic medication management concerns, and a comprehensive interview with an adult with ASD. The book also contains a new theoretical model to ASD which is entitled "The Control Theory of Autism".
Includes bibliographical references and index.
Description based on print version record.
Keywords: Autistic children -- Education; Autism in children -- Treatment; Teaching of autistic students; Education -- Special Education -- Mental Disabilities